Robber Flies, Asilidae (Insecta: Diptera: Asilidae) - E. M. Finn (EDIS)
The robber flies are an abundant and diverse family within the order Diptera that are known for their predatory behavior. Asilidae diversity can be attributed to their broad distribution; most species tend to occupy a selective niche. As their common name implies, robber flies have voracious appetites and feed on a vast array of other arthropods, which may help to maintain a healthy balance between insect populations in various habitats (Joern and Rudd 1982, Shurovnekov 1962). Asilidae adults attack wasps, bees, dragonflies, grasshoppers, other flies, and some spiders. Robber flies are particularly abundant in arid and sunny habitats, which are optimal conditions in which to observe their many morphs and behaviors. This document is EENY-281, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2003.